2022
DOI: 10.1002/hep.32770
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in patients with end‐stage liver disease above model for end‐stage liver disease 3.0 of 40

Abstract: Background and Aims: Since the implementation of the model for endstage liver disease (MELD) score to determine waitlist priority for liver transplant (LT) in 2002, the score has been capped at 40. Recently, the MELD 3.0 score was proposed to improve upon MELD-Na. Here, we examine waitlist mortality and LT outcomes in patients with MELD 3.0 ≥ 40 to assess the potential impact of uncapping the score. Approach and Results: Adult waitlist registrations for LT from January 2016 to December 2021 were identified in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…[4] Patients with alcohol-associated liver disease tended to have higher MELD scores than those with other viral hepatitis, [5] and therefore, they benefited greatly from the MELD allocation system. [6,7] Therefore, we believe that the extent to which MELD 3.0 can improve the existing MELD original system will vary depending on the situation in different countries.Regarding the study that attempted uncapping on patients with a score of 40 or higher on MELD 3.0, [5] additional validation is necessary in Asia. Clinically, patients with a high MELD score are more likely to experience high mortality or complications after transplantation, which may be due to the fact that alcoholic liver disease often progresses to acute-on-chronic liver failure.Our study indicates that the current efforts to improve the allocation system should be continuously implemented for different ethnicities in various regions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[4] Patients with alcohol-associated liver disease tended to have higher MELD scores than those with other viral hepatitis, [5] and therefore, they benefited greatly from the MELD allocation system. [6,7] Therefore, we believe that the extent to which MELD 3.0 can improve the existing MELD original system will vary depending on the situation in different countries.Regarding the study that attempted uncapping on patients with a score of 40 or higher on MELD 3.0, [5] additional validation is necessary in Asia. Clinically, patients with a high MELD score are more likely to experience high mortality or complications after transplantation, which may be due to the fact that alcoholic liver disease often progresses to acute-on-chronic liver failure.Our study indicates that the current efforts to improve the allocation system should be continuously implemented for different ethnicities in various regions.…”
mentioning
confidence: 99%
“…Regarding the study that attempted uncapping on patients with a score of 40 or higher on MELD 3.0, [5] additional validation is necessary in Asia. Clinically, patients with a high MELD score are more likely to experience high mortality or complications after transplantation, which may be due to the fact that alcoholic liver disease often progresses to acute-on-chronic liver failure.…”
mentioning
confidence: 99%
“…For example, the current MELD cap of 40 disadvantages the sickest patients with end-stage liver disease whose MELD scores exceed 40, despite data showing favorable posttransplant survival [7]. Uncapping the MELD may be an easy first step towards a more equitable liver allocation system aligned with the principle of prioritizing the patients most in need [8].…”
mentioning
confidence: 99%
“…However, with the maturity of liver transplantation technology and improvement of perioperative management, will this restriction deprive people with scores above 40 of the chance to survive? To solve this problem, Kim et al [4] examined waitlist mortality and liver transplantation outcomes in patients with MELD 3.0 ≥ 40 and found that uncapping MELD 3.0 improves mortality risk stratification and better represents urgency for liver transplantation for the sickest patients.…”
mentioning
confidence: 99%
“…However, with the maturity of liver transplantation technology and improvement of perioperative management, will this restriction deprive people with scores above 40 of the chance to survive? To solve this problem, Kim et al [4] examined waitlist mortality and liver transplantation outcomes in patients with MELD 3.0 ≥ 40 and found that uncapping MELD 3.0 improves mortality risk stratification and better represents urgency for liver transplantation for the sickest patients.Overall, so far, except for calculation somewhat more complex, MELD 3.0 seems to be completely superior to the original MELD. Therefore, it is worth replacing the existing MELD with MELD 3.0 in regions that currently use the MELD score.…”
mentioning
confidence: 99%